A bead of mass m = 1 kg is confined to a smooth wire in the shape of the curve y = e x . The ambient gravitational acceleration g = 1 0 m/s 2 is in the negative y direction.
At time t = 0 , the bead has zero speed and is located at x = 2 . At what time is the bead located at x = 0 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I used Lagrangian mechanics.
Kinetic energy:
T = 2 1 m ( x ˙ 2 + y ˙ 2 ) = 2 1 m x ˙ 2 ( 1 + e 2 x )
Potential energy:
V = m g y = m g e x
Lagrangian:
L = T − V = 2 1 m x ˙ 2 ( 1 + e 2 x ) − m g e x
Equation of motion:
d t d ∂ x ˙ ∂ L = ∂ x ∂ L
Evaluating results in the following expression for the second time derivative:
x ¨ = 1 + e 2 x − x ˙ 2 e 2 x − g e x
And then numerical integration takes care of the rest. I have shown the explicit Euler technique below. The "k" subscript denotes the present processing interval, and the "k-1" subscript denotes the previous processing interval.
x k = x k − 1 + x ˙ k − 1 Δ t x ˙ k = x ˙ k − 1 + x ¨ k − 1 Δ t x ¨ k = 1 + e 2 x k − x ˙ k 2 e 2 x k − g e x k
@Steven Chase Sir even I did the same though I didn't how to integrate the acceleration because it was in terms of both velocity and x , Sir can you please tell how to integrate further
Log in to reply
You will probably need to use numerical integration to solve. I added a few details to the end of my solution describing this process
Problem Loading...
Note Loading...
Set Loading...
The coordinates of the particle at any general instant are ( x 1 , y 1 ) = ( x , e x ) . The x and y velocity components respectively at that instant are ( x ˙ 1 , y ˙ 1 ) = ( x ˙ , e x x ˙ ) . Therefore, the kinetic energy of the bead is:
T = 2 m ( x ˙ 1 2 + y ˙ 1 2 ) = 2 ( 1 + e 2 x ) x ˙ 2
The potential energy at the same instant is:
V = m g y 1 = 1 0 e x
Applying conservation of energy:
T + V = T i n i t i a l + V i n i t i a l ⟹ 2 ( 1 + e 2 x ) x ˙ 2 + 1 0 e x = 1 0 e 2
Rearranging:
x ˙ 2 = 1 + e 2 x 2 0 ( e 2 − e x ) ⟹ x ˙ = − 1 + e 2 x 2 0 ( e 2 − e x )
The negative sign is introduced because as time increases x decreases. Finally, separating the variables and integrating:
T = ∫ 0 2 2 0 ( e 2 − e x ) 1 + e 2 x d x ≈ 1 . 1 7 4 8 s e c o n d s